Mapping KSPPS Research Using Vosviewer: A Study of the Google Scholar Database 2019-2025 - Rikhe Dwi Nurdiyah; Taufiqur Rahman (Al-Fadilah: Islamic Economics Journal, 2025)
This study aims to map the development of scientific research on Sharia Savings and Loan Cooperatives (KSPPS) in Indonesia by utilizing a bibliometric approach supported by VOSviewer software. Sources of information were obtained from Google Scholar with a publication period between 2019 and 2025. The collection process was carried out using the keyword “KSPPS” along with variations of related terms, which were then filtered to obtain relevant documents in Indonesian. The analysis was conducted by mapping co-authorship, co-occurrence, and citation analysis to identify trends, major themes, prolific authors, and institutions that play an important role in the development of KSPPS research. The results showed that the frequency of publications has increased since 2020, with the most discussed themes including Islamic microfinance management, cooperative governance, and financial literacy. In addition, it was revealed that the network of cooperation between authors is still minimal, indicating the importance of increasing research collaboration between various institutions. This study provides an initial insight into the orientation and shortcomings of Islamic microfinance research, and can serve as a guideline for academics, researchers, and regulators in setting research and policy agendas in the field of Islamic microfinance